Wastewater reclamation in a wafer manufacturing plant - Chen, Jingping. (2008)
This project investigated the potential of reclaiming wastewater from a wafer manufacturing plant using the proprietary Exxflow dynamic membrane technology with the right chemical pre-treatment. Wastewater discharged from the factory benches in the wafer manufacturing process was properly segregated and chemically treated before passing through the Exxflow dynamic membrane. MgCl2 was used for chemical pre-treatment. Based on study carried out, the optimum dosage of MgCl2 was determined as 0.25 ml Mg2+/L.